(untitled) (Bangladesh Journal of Medical Science, 2018)
Alcohol use disorder (AUD) is a major global health concern. Many treatment modalities have been used in past to help decrease the use of alcohol. Recently, a growing interest has been seen in neuromodulation as a novel treatment means to reduce alcohol addiction behavior. Studies on the effect of Transcranial Direct Current Stimulation (tDCS), especially over dorsolateral prefrontal cortex (DLPFC) have been conducted that have shown to reduce craving and relapse behavior in AUD. Adverse effects associated with tDCS are found to be minor and are temporary in nature. However, the results are preliminary as only few studies are done. More research on AUD done using tDCS will help improve our knowledge and understanding on the various factors involved in AUD besides helping to prevent the cycle of craving, relapse and abstinent. Bangladesh Journal of Medical Science Vol.17(1) 2018 p.7-15